Comment on “Philosophical spirit in traditional Chinese drama” - Fang, Wen (2024)
Commented Article: LIU, Rong. Philosophical spirit in traditional Chinese drama. Trans/Form/Ação: Unesp journal of philosophy, Marília, v. 47, n. 4, “Eastern thought”, e0240063, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14667.